AB0685 Secukinumab provides sustained improvements in work productivity and health related quality of life in patients with ankylosing spondylitis: long-term results from measure 1 and measure 2. (15th June 2017) - Deodhar, A; Conaghan, PG; Strand, V; Boonen, A; Ferraccioli, G; Bosch, F Van den; Bhosekar, V; Porter, B; Gandhi, K; Jugl, S
Abstract : Background: Patients (pts) with ankylosing spondylitis (AS) experience significant restrictions in work productivity and health-related quality of life (HRQoL). Secukinumab (SEC) demonstrated rapid improvements in signs, symptoms and physical functioning in pts with AS. 1 Objectives: To assess whether the beneficial effects of SEC on AS signs and symptoms were reflected in improvements in work productivity and HRQoL in the overall population and in TNF inhibitor (TNF)-naïve pts and pts with an inadequate response or intolerance to TNF inhibitors (TNF-IR) for up to 52 weeks (wks) in MEASURE 2 and 104 wks in MEASURE 1. Methods: 371 and 219 pts were randomized to SEC or placebo (PBO) in MEASURE 1 (10 mg/kg IV followed by 150 or 75 mg SC) and MEASURE 2 (150 or 75 mg SC), respectively. At Wk 16, PBO pts were re-randomized to SEC 150 or 75 mg SC (PBO pts with ASAS20 response at Wk 16 were switched to SEC at Wk 24 in MEASURE 1). Productivity was measured using the Work Productivity and Activity Impairment-General Health (WPAI-GH) questionnaire, which includes questions to assess absenteeism, presenteeism and overall work productivity impairment in employed pts, and general activity impairment in all pts during the preceding 7 days (0–100%). HRQoL was assessed with the ASQoL questionnaire (0–18 points). Across both studies, approximately 69% of pts were TNF-naïve and 31% were TNF-IR. Observed data are presented from the full analysis set and in subgroups stratified by prior TNF exposure. Only data with the approved dose (SEC 150 mg) are shown. Results: At baseline (BL), 77 of 125 and 45 of 72 randomized pts were employed and working in the SEC groups in MEASURE 1 and 2, respectively. Improvements in all WPAI domains were observed with SEC in the overall, TNF-naïve and TNF-IR populations at Wk 16 in both studies, and effects were generally sustained through Wks 52 and 104 (Table). In MEASURE 1, activity impairment in the total group improved by 49% and overall work productivity in those employed improved by 45% from BL at Wk 104. Improvements were 51%/49% in TNF-naïve and 42%/19% in TNF-IR pts, respectively. In MEASURE 2, activity impairment and work productivity improved by 43% and 40% vs BL, respectively at Wk 52; improvements in activity impairment/work productivity in TNF-naïve and TNF-IR pts were 49%/54% and 32%/16%, respectively. Similar responses were seen in the other WPAI scores across both studies. Early improvements in ASQoL were sustained through Wk 104 in MEASURE 1 and Wk 52 in MEASURE 2. At Wk 104 of MEASURE 1, ASQoL scores had improved by 48% vs. BL with SEC; improvements were 50% and 39% in TNF-naïve and TNF-IR pts, respectively. Conclusions: SEC provides sustained improvements in work productivity and ASQoL for up to 104 wks among AS pts, regardless of prior TNF exposure. References: Baeten. NEJM 2015;373:2534–48. Disclosure of Interest: A. Deodhar Grant/research support from: Amgen, Abbvie, GSK, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Speakers bureau: Eli Lilly, Janssen, Novartis, Pfizer, UCB, P. Conaghan Consultant for: Abbvie, BMS, Lilly, Novartis, Pfizer, Roche, Speakers bureau: Abbvie, BMS, Lilly, Novartis, Pfizer, Roche, V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, CORRONA, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi, and UCB, A. Boonen Grant/research support from: Merck, Pfizer, Abbvie and Amgen, Speakers bureau: Sandoz, Janssen, Lilly, G. Ferraccioli Grant/research support from: BMS, Roche, MSD, Speakers bureau: AbbVie, Pfizer, UCB.Roche, MSD, Eli Lilly, GSK, Novartis, F. Van den Bosch Consultant for: Abbvie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, UCB, V. Bhosekar Employee of: Novartis, B. Porter Shareholder of: Novartis, Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis